2021
DOI: 10.1038/s41598-021-90320-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smartphone-based stress management programs on depression and anxiety of hospital nurses in Vietnam: a three-arm randomized controlled trial

Abstract: There are growing concerns on stress among nurses in low- and middle-income countries (LMICs) in South-East Asia. It is important to improve mental health among nurses in these countries. The objective of this study was to examine the efficacy of two types of newly developed smartphone-based stress management programs in improving depressive and anxiety symptoms among hospital nurses in Vietnam. This study was a three-arm (including two intervention groups and one control group) randomized trial. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…It might have been better to interview patients with perinatal depression to determine the topics. Furthermore, compared with our previous smartphone based RCT, 32 the completion rate in this study was relatively low. This might be explained by the fact that many pregnant women participated in the study in a casual manner and did not have a very high commitment to completion.…”
Section: Discussionmentioning
confidence: 65%
“…It might have been better to interview patients with perinatal depression to determine the topics. Furthermore, compared with our previous smartphone based RCT, 32 the completion rate in this study was relatively low. This might be explained by the fact that many pregnant women participated in the study in a casual manner and did not have a very high commitment to completion.…”
Section: Discussionmentioning
confidence: 65%
“…A previous randomized controlled trial (RCT) reported that an Internet cognitive behavioral therapy (iCBT) program reduced perceived work-related stress among nurses in the US [14]. We also found that a selfguided iCBT program reduced depression of nurses in Vietnam at 3-month follow-up [15]. However, these studies were conducted before the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 79%
“…To date, the region had a largest total number of mortality due to COVID-19 following Europe and Americas [18]. We intend to test the effectiveness of a smart-phone iCBT stress management program on improving mental health of nurses in this region in the COVID-19 pandemic, by using a modified version of our previous iCBT program for nurses in Vietnam [15,19] adapted to the COVID-19 situations. To increase the generalizability of the study finding, we select two rapidly industrialized middle-income countries of the region, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, mostram efeitos positivos de curto e médio prazo na satisfação por compaixão, estresse traumático secundário e saúde mental. Até mesmo, o desenvolvimento de programas para smartphones, com cunho educacional demonstrou eficácia na melhora de sintomas depressivos (Fu et al, 2021;Imamura et al, 2021).…”
Section: Discussionunclassified